Chapter Cheminer dans les espaces pastoraux du Buccolicum carmen avec Boccace - CHAUVIN, Claire (Studi e saggi, 2021)
The present article aims to present Boccaccio's Buccolicum carmen as a main work in his latin production, inspired by Vergil and his followers during the Middle Age. Through the allegorical path, focused on the shepherd's environment, Boccaccio first defines a model of power embodied by the king-shepherd. Moreover, he tries to convert his readers, as well as himself, into a better way of life related to Vergil's one and close to the eremitic model. By doing so, he accomplishes himself as a poeta-theologus, as exposed by Dante.